Status dan Perlindungan Hukum Anak dalam Kandungan Seorang Wanita yang Belum Menikah (Studi Kasus: KUA DUNGINGI) - Susanti I. Botu; Nur Mohamad Kasim; Zamroni Abdussamad (Universitas Sains dan Teknologi Komputer, 2023)
This study discusses the legal status and protection of children in the womb of an unmarried woman in Kua Dungingi. The purpose of this study is to find out how the status and legal protection of children in the womb of an unmarried woman are viewed from the perspective of positive law and Islamic law. The research method used is an empirical research method. The status of children of women who are pregnant out of wedlock is to have the same rights as other children as in Article 1 number 12 of Law Number 23 of 2022 concerning child protection states that ha kana are part of of human rights that must be guaranteed, protected and fulfilled by parents, family, society, government and the state. However, after the birth of a child from a woman who is pregnant out of wedlock, there will be several obstacles in terms of administrative arrangements, such as processing birth certificates. Then, the legal arrangements for pregnant women out of wedlock are based on positive law, the compilation of Islamic law, and Islamic law in Indonesia, there is a difference in positive law. regulated more towards the crime of adultery, while in the compilation of Islamic law one can marry a woman who is pregnant out of wedlock, and in Islamic law itself there are two opinions, namely there are those who allow it and there are those who forbid it.